Paget’s disease of the breast: a contemporary perspective - O. O. Yemelyanova; A. D. Zikiryakhodzhaev; N. N. Volchenko; V. V. Efanov (Исследования и практика в медицине, 2023)
The treatment strategy for Paget’s breast cancer (PBC), as for other morphological forms, is determined by the spread of the invasive tumor process, as well as the absence or presence of adverse factors. Significant prognostic factors, e.g. the invasive component of Paget’s cancer, the involvement status of regional lymph nodes, morphological criteria, the grade of malignancy, overexpression of epidermal growth factor Her2/neu, the presence of BRCA 1/2 and CHEK2 gene mutations, as well as age, affect the prognosis of Paget’s disease. According to various sources, PBC in 90–98 % is combined with invasive or non‑invasive breast cancer. For the most part, the lesion is multifocal. There’s high expectation for PBC to form tumor node. A palpable tumor node in the mammary gland is detected in half of the patients. PBC has certain features and specificity in relation to treatment methods. The method of radical surgical treatment of patients is primarily based on performing oncoplastic resections. Sufficient breast volume is a significant criterion for the possibility of performing an organ‑ preserving operation. The organ‑ preserving treatment is oncologically safe in case of PBC. The removal of the nipple‑ areolar complex is mandatory in case of PBC. It is possible to improve survival statistics by analyzing the biological characteristics of the tumor and developing a more accurate approach to the treatment of patients in this category. Determining clear indications for organ‑p reserving operations is the main opportunity to improve the quality of life of patients and their further rehabilitation.